Nanoscale topotactic phase transformation modulated by triboelectrification for high memory storage. (March 2023) - Ren, Lele; Guo, Pengwen; Jia, Mengmeng; Xiao, Junfeng; Meng, Dehuan; Liu, Yudong; Wang, Wei; Guo, Di; Wang, Zhong Lin; Zhai, Junyi
Abstract: The applications of triboelectrification have attracted much attention due to the direct regulation of charges with external mechanical stimuli. Atomic force microscopy (AFM) is an effective method to achieve controllable nanoscale friction. Herein, we demonstrated a phase transformation from the brownmillerite SrCoO2.5 (BM-SCO) to perovskite SrCoO3-δ (PV-SCO) as modulated by nanoscale friction with the contact mode AFM. Besides, such phase transformation can be reversible by applying a negative voltage. More importantly, when defining the surface potential of different phases as binary bits of "1" and "0", we could reach high-density data storage as the surface charge is constantly written and erased in nanoscale regions. This work opens a new way for the regulation of phase transformation by triboelectrification, and realizes the surface charge patterning based on different phases at the nanoscale by AFM tip friction, which is of great significance for the application of nano devices in high-density data storage. Graphical Abstract: The nanoscale phase transformation of SrCoO2.5 can be realized by AFM tip friction. And through the writing and erasing of surface charges, a binary-based data storage array can be realized, which is of great significance for phase transformation materials in high-density data storage. ga1 Highlights: A nanoscale phase transformation of SrCoO2.5 is induced by triboelectrification. The AFM tip friction has great flexibility for the patterned charge writing. The high-density data storage is achieved when the surface charges are written and erased in nanoscale.